Preventing and fighting stigma: a lesson from the first Mpox in Veneto region of Northeast Italy—A case report - Baldovin, Tatjana; Girolametto, Gloria; Geppini, Ruggero; Bordignon, Matteo; Alaibac, Mauro (Frontiers in Public Health, 2023)
Since the 1970s, Mpox (human Monkeypox) has been referred as a zoonotic endemic disease of specific areas of Africa, until early 2022, when a worldwide epidemic outbreak developed. There are many hypotheses on how Mpox could spread to non-endemic regions; the dominant theory is that it spread from UK and Spain among men who have sex with men (MSM). Therefore, the first clinical case in Veneto region (NE Italy) was analysed, which represents a typical case report of the ongoing outbreak, with lesions located mainly in sexual regions (genital and oral). This case report seeks to highlight new challenges of Mpox, as it seemed to differ from the previous classic manifestation. Indeed, although the patient achieved ad-integrum restitution of lesions and complete recovery from the disease, it is deemed necessary to offer communication strategies to involve a heterogeneous audience, based on different risks of exposure but without stigmatizing attitudes, avoiding the mistakes made with HIV. The need for broad public involvement is demonstrated by the identification of Mpox even in "anomalous cases”. Stigma could be an obstacle in engaging patients in appropriate care and in getting honest answers while contact tracing, as happened in our patient's case, so WHO recently renamed Monkeypox as Mpox. Abnormal outbreaks in non-endemic countries, with no causal links, must become a warning signal for governments and health policies to design national plans for the management of unexpected outbreaks. For an effective public health response, health institutions must communicate effectively, focus on changes and prevention measures, and formulate a plan based on equity and inclusion of the most vulnerable.